Construção de uma cabana em Light Steel Frame: dimensionamento e análise técnica estrutural - Menegat, Douglas (My University, 2024)
The construction system of light steel structures, known as Light Steel Framing, also referred to as Light Steel Frame (LSF), enables the rationalization of civil construction through the industrialization of building elements. Aiming to increase construction efficiency, boost productivity, reduce waste, and meet the high demand for buildings, especially due to the housing deficit in Brazil, the LSF system, composed of cold-formed profiles (CFP), presents itself as a viable structural solution. In this context, this work analyzes the design and construction of a cabin in LSF, exploring the particularities of this construction method, such as materials, terminology, design features, and calculation considerations. The choice of ZAR230-G275 steel, with a minimum yield strength of 230 MPa and G275 zinc coating, was based on its excellent mechanical strength and durability, providing corrosion protection and ensuring the structure's lifespan. The material's lightness facilitates handling and installation, resulting in reduced construction time and costs. The versatility of ZAR230-G275 steel allows for various applications, including profiles for walls, floors, and roofs. In the development of this work, the structural modeling of the cabin was carried out using 3D programs (Revit and SolidWorks), based on Brazilian standards ABNT NBR 8800:2024, NBR 14762:2010, NBR 15253:2014, NBR 15575:2013, NBR 6120:2019, NBR 6123:2023, and the specific standard for the system, NBR 16970:2022. The methodology involved defining the geometric and mechanical characteristics of the profiles used, applying load combinations as specified by the standards, and conducting stress and displacement analyses using the finite element method. During the process, it was possible to map zones of greater structural sensitivity, such as window lintels, wall structures, and roofs, allowing for the proper technical detailing of each element. The evaluation of the resistance forces for each profile and the maximum displacements of the structure was discussed to enable the proper sizing of the construction elements. The results obtained from simulations in the SolidWorks program indicated that the maximum displacements of the structural elements were within the limits allowed by the standards, ensuring the cabin's stability and safety. It was concluded that the sizing of the structural profiles strictly followed Brazilian technical standards, ensuring the adequacy of the forces and the safety of the structure. The structural analysis demonstrated that the LSF system is effective for small-scale projects, highlighting the potential of this construction method to meet housing demands with efficiency, quality, and sustainability. [resumo fornecido pelo autor]
O sistema construtivo de estruturas leves em aço, conhecido como Light Steel Framing, também conhecido como Light Steel Frame (LSF), possibilita a racionalização da construção civil através da industrialização dos elementos de uma edificação. Com o objetivo de aumentar a eficiência construtiva, elevar a produtividade, reduzir o desperdício e atender à alta demanda por edificações, especialmente devido ao déficit habitacional no Brasil, o sistema LSF, constituído por perfis formados a frio (PFF), se apresenta como uma solução estrutural viável. Neste contexto, este trabalho analisa o dimensionamento da construção de uma cabana em LSF, explorando as particularidades desse método construtivo, como materiais, terminologias, características de projeto e considerações de cálculo. A escolha do aço ZAR230-G275, com limite de escoamento mínimo de 230 MPa e revestimento de zinco G275, foi fundamentada por sua excelente resistência mecânica e durabilidade, proporcionando proteção contra corrosão e garantindo a vida útil da estrutura. A leveza do material facilita o manuseio e a instalação, resultando em redução de tempo e custos de construção. A versatilidade do aço ZAR230-G275 permite diversas aplicações, incluindo perfis para paredes, pisos e coberturas. No desenvolvimento deste trabalho, a modelagem estrutural da cabana foi realizada utilizando programas 3D (Revit e SolidWorks), com base nas normas brasileiras ABNT NBR 8800:2024, NBR 14762:2010, NBR 15253:2014, NBR 15575:2013, NBR 6120:2019, NBR 6123:2023 e a norma específica para o sistema, a NBR 16970:2022. A metodologia envolveu a definição das características geométricas e mecânicas dos perfis utilizados, a aplicação das combinações de carregamento conforme especificado nas normas, e a realização de análises de esforços e deslocamentos utilizando o método dos elementos finitos. Durante o processo, foi possível mapear zonas de maior sensibilidade estrutural, como vergas de esquadrias, estrutura de paredes e coberturas, permitindo o detalhamento técnico adequado para cada elemento. A avaliação dos esforços resistentes para cada perfil e dos deslocamentos máximos da estrutura foi discutida para possibilitar o dimensionamento adequado dos elementos da construção. Os resultados obtidos nas simulações no programa SolidWorks indicaram que os deslocamentos máximos dos elementos estruturais ficaram dentro dos limites permitidos pelas normas, garantindo a estabilidade e segurança da cabana. Concluiu-se que o dimensionamento dos perfis estruturais seguiu rigorosamente as normas técnicas brasileiras, assegurando a adequação dos esforços e a segurança da estrutura. A análise estrutural demonstrou que o sistema LSF é eficaz na aplicação para projetos de pequeno porte, evidenciando o potencial desse método construtivo em atender a demandas habitacionais com eficiência, qualidade e sustentabilidade. [resumo fornecido pelo autor]
Keywords: Projeto estrutural; Engenharia civil